A Study On Utility of Web-Based Drug Warehouse Management System (E-Aushadhi) In A Peripheral Hospital of Metropolitan City of Maharashtra - Pande, Bhanupriya; Mishra, Sandeep; Dhanusu, Subashri (National Journal of Community Medicine, 2022)
Introduction: An E-Aushadhi management system based on database was introduced in urban health centre for managing stock outs. This study was conducted to assess utility of web-based drug warehouse management system in a peripheral hospital. Objectives: The objectives of this study were to assess the perceived benefits and difficulties by health care providers expected in introducing a web-based Supply Chain Management System (E-aushadhi) and to identify the factors which will govern successful transition from current system of drug logistics management to web-based system. Methods and materials: In this study Focus Group Discussion was conducted with the staff members of an urban health centre who were working on a similar web-based platforms. There are four teams each comprising 3-5 members. Results: Themes and subthemes were made based on the transcripts analysed. It is perceived that with introduction of web-based drug warehouse system, accuracy of the data can be well assured as manual errors can be reduced a lot. Quality of stock maintenance will increase and will prevent stock outs Conclusion: The accuracy and transparency of drug stock maintenance will be increased while technical challenges such as internet availability, technician availability and training of personnel are perceived barriers.